Coronary atherosclerosis with vulnerable plaque and complicated lesions in transplant recipients: new insight into cardiac allograft vasculopathy by optical coherence tomography - Cassar, Andrew (Oxford University Press, 2013)
AIMS: Cardiac allograft vasculopathy (CAV) is a major limitation to long-term survival following cardiac transplantation. Conventional imaging modalities such as angiography and intravascular ultrasound fail to characterize CAV plaque morphology. Our aim was to characterize CAV in vivo using the high spatial resolution of intracoronary optical coherence tomography (OCT). METHODS AND RESULTS: We prospectively enrolled 53 cardiac transplant patients to undergo OCT of the left anterior descending coronary artery (LAD) in addition to annual CAV screening by coronary angiography and intravascular ultrasound (IVUS). The proximal 30 mm of the LAD was divided into three segments of 10 mm each (n = 156). Segments with CAV plaque on IVUS were analysed by OCT for specific CAV morphological characteristics within the framework of three groups according to follow-up time after heart transplantation: (i) 0–3 months (n = 18), (ii) 12–36 months (n = 55), and (iii) ≥48 months (n = 83). The prevalence of atherosclerotic characteristics such as eccentric plaques, calcification, and lipid pools increased from 6, 0, and 6% in group 1 to 78, 42, and 61% in group 3, respectively (all P < 0.001). The prevalence of vulnerable plaque features such as thin-cap fibroatheroma, macrophages, and microchannels increased from 0% in group 1 to 12, 29, and 33% in group 3, respectively (P = 0.19, P = 0.006, and P = 0.003). Complicated coronary lesions such as intimal laceration, intraluminal thrombus, and layered complex plaque increased from 0% in group 1 to 18, 19, and 57% in group 3 (P = 0.009, P < 0.001, and P < 0.001). Plaque rupture was identified in 4% of group 3 segments. CONCLUSION: The current study gives new insight into CAV that extends far beyond the current concept of concentric and fibrosing vasculopathy, that is, the development of atherosclerosis with vulnerable plaque and complicated coronary lesions.